Punjab's Linguistic Land Scape: Postcolonial Reading of Literary, Political and Social Contexts - Sajid Javed (بازیافت)
<span style="mso-bidi-font-size: 12.0pt; line-height: 150%; mso-ascii-font-family: "Times New Roman"; mso-ascii-theme-font: major-bidi; mso-hansi-font-family: "Times New Roman"; mso-hansi-theme-font: major-bidi; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: major-bidi; mso-bidi-language: ER;">Fort William College was formed in 1800 at Calcutta by the personnel of East India Company for the main purpose of indigenous languages acquisition to its civil and military officials. The various departments like Hindoostanee, Punjabi, Persian, Arabic and other local languages were established for this purpose. John Gilchrist was the head of Hindoostanee (Urdu) language department. He devise the refined dialect of Hindoostanee language named Urdu here which was the language of command for northern Indian parts in colonial period. This language was imposed as an official language of different Indian parts included Punjab. Punjab was being governed by Maharaja Ranjeet Singh at that time. Persian was the official and Punjabi was the language of common man at that time. The literacy rate of Punjab was above eighty percent at that time. Since 1857, the language landscape of Punjab was changed by the British Rulers and The Persian and Punjabi Language was replaced by Urdu Language which was not the language of commoners here. There were two types of views from local intelligentsia as well as The British officials to change the language identification of this province or not. Due to adopt the Urdu language, the literacy rate of Punjab was reduced automatically. This action by the rulers changed political as well as the social scenario of this region. The third language Saraiki of the western part of Punjab was also accepted serious changes in itself. After 1947, The East Punjab restore the real Punjabi Language in India because it was the religious and first language of Sikh community, but this Language change was continued in Punjab province. This colonial agenda was the effective reason for the dramatic linguistic changes in 19th and 20th century in Punjab. The historical and socio linguistics changes will be observed and discussed in colonial and pre-colonial period in this article. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <w:LsdException Lock